Uninvestigated Dyspepsia and Heartburn Overlap Syndrome at Industrial Hub of Eastern Siberia - V. V. Tsukanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. A study of the overlap syndrome of uninvestigated dyspepsia and heartburn at an industrial hub city of Eastern Siberia.Materials and methods. A total of 1,382 subjects (684 men and 698 women, mean age 40.6 years) were randomly selected and examined for the central district of Krasnoyarsk. The clinical check-up and interviewing results were registered with a standard questionnaire. Heartburn was diagnosed as per the Montreal Consensus. Since no endoscopic patient examination had been performed, dyspepsia was assumed uninvestigated. Dyspepsia was diagnosed as per the Rome IV criteria. The study conduction complied with ethical standards. Each participant signed an informed examination consent, in accordance to the regulations by the World Medical Association’s Declaration of Helsinki. The survey data were analysed with common statistical methods.Results. Heartburn, uninvestigated dyspepsia and their overlap syndrome had prevalence of 12.4, 21.1 and 5% in study population, respectively. Uninvestigated dyspepsia was registered in 40.4% patients with and 18.4% — without heartburn (p < 0.001). The risk factors of overlap syndrome were age >40 years (p = 0.002), obesity (p = 0.002), nonsteroidal anti-inflammatory drug and/or aspirin intake (p = 0.004) and tobacco smoking (p = 0.007). Among total patients with the heartburn/uninvestigated dyspepsia overlap syndrome, only 33.3% systemically had proton pump inhibitors, and only 17.4% had a prokinetic therapy.Conclusion. The heartburn/uninvestigated dyspepsia overlap syndrome is an actual issue in the Krasnoyarsk population. Attention is warranted to this problem to optimise treatment and prevention measures.